2011
DOI: 10.1155/2011/107303
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Sources forMelipona capixabaMoure & Camargo: An Endangered Brazilian Stingless Bee

Abstract: Pollen samples were collected in three different periods from 11 Melipona capixaba Moure & Camargo hives and analyzed with melissopalynological methodology. A total of 33 pollen types were identified, of which 23 genera and 15 families were identified. The following families showed the highest pollen richness: Fabaceae (7), Myrtaceae (3), Solanaceae (3), Arecaceae (2), Asteraceae (2), Euphorbiaceae (2), Melastomataceae/Combretaceae (2), Rubiaceae (2), and Sapindaceae (2). The most frequent pollen types (>45%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
16
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 14 publications
6
16
0
4
Order By: Relevance
“…Our results corroborate the results found by these authors, because we also observed these pollen types in geopropolis of Melipona fasciculata from Maranhão, although in different percentages. The preference of Arecaceae, Myrtaceae, Melastomataceae and Solanaceae as pollen resources by Melipona is well-known (Kleinert-Giovannini & Imperatriz-Fonseca, 1987;Guibu et al, 1988;Ramalho et al, 1989;Carvalho et al, 2001;Luz et al, 2011), which may also indicate the contamination of geopropolis by pollen from food stocks of the beehives.…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborate the results found by these authors, because we also observed these pollen types in geopropolis of Melipona fasciculata from Maranhão, although in different percentages. The preference of Arecaceae, Myrtaceae, Melastomataceae and Solanaceae as pollen resources by Melipona is well-known (Kleinert-Giovannini & Imperatriz-Fonseca, 1987;Guibu et al, 1988;Ramalho et al, 1989;Carvalho et al, 2001;Luz et al, 2011), which may also indicate the contamination of geopropolis by pollen from food stocks of the beehives.…”
Section: Discussionmentioning
confidence: 99%
“…Regional data were presented by Barth & Luz (1998) with regard to pollen collection inside mangrove areas, Barth (2004) in a review, Modro et al (2007), Luz et al (2007) in a forested area of Rio de Janeiro State, Melo et al (2009) in São Paulo State, Barth et al (2009), Luz et al (2010 in Minas Gerais State, Barth et al (2010) with regard to the technical processing of pollen loads, Luz et al (2011) in Espírito Santo State, Boff et al (2011) The present study aimed to investigate the botanical and geographical origins of bee pollen collected in four Brazilian macro-regions. This study aimed to provide also results that will contribute to improve the certification of this bee product and the preservation of the native vegetation.…”
mentioning
confidence: 99%
“…Similarly, more than 75% of Myrtaceae pollen grains was found in the honey and in the larval food from five species of Melipona in the Amazon forest (Cortopassi-Laurino et al, 2007). Luz et al, (2011) and Serra et al, (2012) also found preference for Myrtaceae pollen in Melipona capixaba Moure and Camargo. According to Roubik (1989) the foraging behavior of a bee is determined by the resources it has access, being influenced by the quality, dispersion, quantity and competition for these resources plus the environmental conditions.…”
Section: Discussionmentioning
confidence: 80%